Understanding The Perpetrators And Victims of Cyberbullying Through Facebook in The City of Palu - Muhammad Khairil (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2018)
Communication Technology is growing rapidly, it reflects the social behavior of people in this digital era. Harassment is common in real world, thus it is also often in virtual life which leads to cyber harassment or cyberbullying. This research focuses on the Facebook users in reaction to the electing stimulus they got. The behavior of cyberbullying communication is an adverse behavior not only for the object (victim) but also the subject (actor) of cyberbullying itself. The purpose of this research is to identify the respondent behavior and as operant behavior. This research utilize a descriptive-qualitative approach using case study method. The electing stimulations found in the form of online (online interaction through Facebook) or offline (based on real world interaction, not via Facebook) stimuli. Based on the observation and interview with respondent, it can be concluded that there are three forms of cyberbullying communication behavior by youngadults in Palu City that occurred on Facebook, namely impersonation, denunciation, and flame war.